CCC-NHC Au(III) pincer complexes as a reliable platform for isolating elusive species - Valdés, Hugo; Alpuente, Nora; Salvador, Pedro; Hashmi, A. Stephen K.; Ribas, Xavi (Chemical science, 2024)
The reactivity of unprecedented CCC-NHC Au(III) pincer complexes has been investigated, employing a novel methodology for their preparation. Notably, this marks the inaugural case of CCC-NHC Au(III) pincer complexes with a central aryl moiety where the two arms of the pincer ligand consist of N-heterocyclic carbenes (NHC). The stability conferred by the CCC-NHC ligand facilitated the isolation of elusive Au(III) species, encompassing Au(III)-formate, Au(III)-F, Au(III)-Me, and Au(III)-alkynyl. Our study also unveiled the elusive Au(III)-H species, offering valuable insights into its formation, stability, and reactivity. While the CCC-NHC Au(III)-H complex remains stable at room temperature, its decomposition becomes conspicuous at elevated temperatures (>60 °C), exhibiting a more pronounced tendency under acidic conditions compared to basic ones. Through comprehensive experiments, we indirectly demonstrated the potential of Au(III)-formate to undergo β-hydride elimination, becoming a key step in the dehydrogenation of formic acid. Theoretical calculations revealed variations in the reactivity of Au(III)-H species towards sodium hydride and formic acid, highlighting a link between σ-donation from the pincer ligand and reaction energetics. Pincers with lower electron donation favored the reaction with sodium hydride but impeded the reaction with formic acid, whereas those with higher electron donation exhibited the opposite behavior. Additionally, the CCC-NHC Au(III) pincer complex exhibited Lewis acid behavior, catalyzing the synthesis of phenols. In summary, the CCC-NHC Au(III) pincer complex emerges as a versatile platform for isolating reactive species and unraveling elementary catalytic steps.